Analisis Penilaian Laporan Akuntabilitas Kinerja Instansi Pemerintah (LAKIP) Komisi Pemilihan Umum Kota Bogor Dibandingkan Dengan Komisi Pemilihan Umum Kota Bandung - Tresnowati, Mega; Munawar, Aang; ., Yudiana (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
Purpose: to analyze the assessment of the the Government Institution Performance Accountability Report of Bogor General Election Commissions compared to the Bandung General Election Commissions which are used to measure the success of performance achievements and budget realization of a government agency to realize the principles of good governance and to understand the use of performance reports in improving the quality of performance in the next period. Design/metholodology/approach: This research use qualitative approach with case study method in Bogor General Election Commissions and Bandung General Election Commissions. Data collection use document review.Finding: The results of the assessment analysis of the Government InstitutionalPerformance Accountability Report (LAKIP) of the Bogor City KPU compared to the Bandung City KPU showed that the achievement of the performance of the Bogor City KPU and the Bandung City KPU on the strategic targets set in the performance agreement generally achieved the targets and in accordance with the predetermined plan, but there are also activities that do not reach the target, this is due to experiencing constraints caused by several factors in the assessment process of Government Institution Performance Accountability Report (LAKIP). Originiality/value: to maintain and improve the performance achievement it needs cooperation, coordination, improvement and commitment off all Bogor General Election Commissions and Bandung General Election Commissions employees